Procedimentos operacionais para desenvolvimento de projetos de inovação tecnológica no SENAI RR - Uchôa, Antônio Robério Barbosa (2019)
The National Service for Industrial Learning (SENAI) is the largest vocational education complex in Latin America and one of the five largest vocational education complexes in the world. Using its own methodology of Professional Education, aimed at developing the culture of innovation and technology-based entrepreneurship in Brazil, SENAI increasingly seeks to enhance students' creativity in the face of the needs of Brazilian industry and the new technological challenges of the 4th Industrial Revolution. by preparing them to innovate. This is what the SENAI Professional Education Methodology (MSEP) advocates, which has among the guiding principles of its practice, the encouragement of creative thinking and innovation. Although initiatives with projects within the so-called SENAI Innovation Saga are part of SENAI schools' daily life, teachers and students face many difficulties in developing innovation projects. To help alleviate these difficulties, a manual for developing technological innovation projects was prepared to be used initially in SENAI RR schools. The product was developed based on a survey of SENAI Nacional documents, project documents developed in SENAI RR in 2017 and 2018 and based on information gathered from the teachers and pedagogical staff who worked as project advisors in that period. After analysis and treatment of the collected information, the manual of procedures for elaboration of Technological Innovation Projects was elaborated.